Method for treating sewage by using efficient grafting type natural polymeric flocculant

By grafting modification on natural polymer flocculants, the metal ion residue problem caused by inorganic flocculants and the lack of high cost of synthetic organic flocculants are solved, and the water treatment effect is achieved with high efficiency, environmental protection and low cost.

CN119841423AInactive Publication Date: 2025-04-18NANJING UNIV +1

Patent Information

Application Number
CN202311343938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing water treatment technologies, commonly used inorganic flocculants will cause trace metal ions to remain, affecting the safety of water quality. At the same time, the cost of synthesizing organic polymer flocculants is high and may have toxic risks.

Method used

High-efficiency grafted amphoteric natural polymer flocculant is used. This flocculant improves flocculation performance and water solubility by grafting and introducing water-soluble polymer chains on the natural polymer main chain, and reduces the amount of acrylamide used by chemical modification.

Benefits of technology

It achieves efficient flocculation effect, reduces the risk of metal ion residue, and has good salt resistance and a wide range of application. It has functions such as flocculation, metal ion adsorption, antibacterial, deodorization, decolorization and reducing COD value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841423A_ABST
    Figure CN119841423A_ABST
Patent Text Reader

Abstract

The invention relates to a method for treating sewage by using an efficient grafting type natural polymeric flocculant, and belongs to the technical field of environmental protection. Not only is the flocculation performance of the material improved, but also the dissolving performance of natural macromolecules is improved; the high polymer material is wide in source and low in price, and the flocculant material has relatively high cost performance; the natural polymer has biodegradability and is non-toxic, so that secondary pollution to the water body is avoided; compared with a polyacrylamide flocculant, the mass proportion of the added acrylamide in the final flocculant is greatly reduced, and the pollution risk of an acrylamide monomer is greatly reduced; the method has the characteristic of high efficiency, and the putting amount is low and is generally 0.1-0.5 mg / L; the composite material is suitable for treating water bodies with different charges, has good salt resistance and a wide pH range, can be applied within 2-11, and can be used for treating kaolin turbid liquid, a humic acid aqueous solution and a hematite powder turbid liquid, and the pollutant removal rate of the treated water sample is higher than 98.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for using a high-efficiency grafted natural polymer flocculant for sewage treatment, belonging to the technical field of environmental protection. Background Art

[0002] Effective sewage treatment has important practical significance for ensuring people’s drinking water safety and improving their quality of life.

[0003] In conventional water treatment, flocculation is an essential step. In this process, the choice of flocculant directly determines the flocculation effect, and is also the key and core foundation of flocculation water treatment technology. At present, inorganic flocculant materials (mainly aluminum salts and iron salts) have the advantages of good flocculation effect and relatively low price, and are still the most commonly used flocculants in current water treatment. However, in the use of such flocculants, trace amounts of aluminum ions or iron ions will inevitably remain in the water, causing the metal ion content in the water to increase. If people drink this water for a long time, it will definitely damage their health. For example, the deposition of aluminum ions in the human body can cause Alzheimer's disease. Compared with the old standard, the new standard has clear regulations on the residual amounts of aluminum ions and iron ions. In addition, synthetic organic polymer flocculants, such as polyacrylamide, are more effective than inorganic flocculants and require less dosage, but are more expensive. Moreover, although the polymer itself is non-toxic, the monomers contained in the polymer that do not participate in the reaction, such as acrylamide, are highly toxic (although the flocculant of the present invention also has acrylamide segments, the mass proportion of the added acrylamide in the final flocculant is greatly reduced, greatly reducing this risk). Therefore, it is now generally believed that aluminum salts and polyacrylamide should be used with caution in water treatment processes to purify water.

[0004] Natural polymers are macromolecules in animals, plants and microbial resources in nature, such as starch, chitin, cellulose and alginic acid. They are easily decomposed into water, carbon dioxide, etc. after being discarded, and they are widely available, non-toxic and environmentally friendly materials. In addition, it is worth mentioning that natural polymer materials are a type of renewable resources that are completely independent of petroleum resources, which can be said to be inexhaustible. It is precisely because of the above-mentioned excellent properties of natural polymer materials that they are currently widely used in many fields such as biology, medicine and food processing. In addition, natural polymers have a good flocculation effect due to the large number of free active groups distributed on the molecular chain. In fact, natural polymers have been used as water purifiers as early as ancient times. In modern times, due to the rapid development of inorganic flocculants and synthetic polymer flocculants, the research on natural polymer flocculants has entered a stagnant period. In recent years, with the increasing severity of environmental pollution, natural polymer materials have once again become one of the hot spots in the current research and development of water treatment agents due to their environmental protection characteristics, and have been regarded as one of the best alternative materials for the currently used inorganic flocculants. Since the 1970s, countries such as Japan, the United States, the United Kingdom, and France have begun to use natural polymer flocculants in wastewater treatment. my country is extremely rich in natural polymer resources, but relatively speaking, there are few studies in this area, and most of them remain in the laboratory research stage, with few practical applications. Today, the Chinese government attaches great importance to the quality of drinking water and has announced the implementation of new drinking water hygiene standards and industry emission standards, which undoubtedly provides a good opportunity for the further development of natural polymer flocculants.

[0005] However, natural polymers also have many shortcomings in practical applications, such as: most natural polymers themselves are uncharged, chemically inactive, poorly soluble, relatively low molecular weight, and narrow applicable pH range, etc. In view of these shortcomings, people use chemical modification methods to improve performance. Among them, compared with other modified natural polymer materials (such as non-grafted, anionic, cationic, etc.), amphoteric natural polymers not only have greatly improved water solubility, but also have the dual characteristics of anionic and cationic groups, which are suitable for treating water bodies with different charges and have good salt resistance; and their scope of application is also wide, and they can be used in acidic and alkaline media. In addition, amphoteric natural polymers also have good complexation, and can produce complexation with transition metal ions, anionic / cationic electrolytes, humic acid substances, and surfactants in water, and can also achieve the removal of water-soluble organic pollutants. In this way, amphoteric natural polymer flocculants have many functions such as flocculation, metal ion adsorption and removal of water-soluble organic matter, and have great application prospects. In addition, based on the bonding and bridging mechanism in the flocculation effect of polymer flocculants, other polymer chains, especially water-soluble polymer chains, are grafted onto the main chain of natural polymers, which can not only increase the molecular weight of the polymer and enhance the bonding, bridging and flocculation effect, but also further improve the water solubility of natural polymers. Summary of the invention

[0006] The present invention provides a method for using an efficient grafted natural polymer flocculant for sewage treatment, and the obtained flocculant has good flocculation effect. The efficient grafted amphoteric natural polymer flocculant material of the present invention not only improves the flocculation performance of the material, but also improves the solubility performance of the natural polymer; the polymer material is widely available and inexpensive, and the grafted amphoteric natural polymer flocculant material has a high cost performance ratio; the natural polymer is biodegradable and non-toxic in itself, and will not cause secondary pollution to the water body; compared with the polyacrylamide flocculant, the mass proportion of acrylamide added to the final flocculant in the product of the present invention is greatly reduced, which greatly reduces the pollution risk of acrylamide monomer; the product has many functions such as good flocculation, metal ion adsorption, antibacterial, deodorization, decolorization and effective reduction of COD value; the product has the characteristics of high efficiency and low dosage, generally 0.1-0.5 mg / L; the product can be suitable for treating water bodies with different charges, has good salt resistance, and has a wide pH range, which can be applied within 2-11.

[0007] In order to solve the technical problem of the present invention, the technical scheme proposed is: a method for using a high-efficiency grafted natural polymer flocculant for sewage treatment, using a high-efficiency grafted natural polymer flocculant for sewage treatment, wherein the flocculant uses kaolin suspension, humic acid aqueous solution and hematite suspension as sewage samples to be treated, and for kaolin suspension, when the flocculant dosage is 0.3 mg / L, the flocculation effect is the best, and the turbidity removal rate of the water sample is more than 98.5%; for humic acid aqueous solution, when the flocculant dosage is 2.5 mg / L, the flocculation effect is the best , the humic acid removal rate of water samples is more than 98.5%; for hematite suspension, when the flocculant dosage is 0.4mg / L, the flocculation effect is the best, and the turbidity removal rate of water samples is more than 98.5%; for kaolin suspension, in the range of pH = 2-10, the turbidity removal rate of water samples after treatment is higher than 98.5%; for humic acid aqueous solution, in the range of pH = 2-10, the humic acid removal rate of water samples after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 3-11, the turbidity removal rate of water samples after treatment is higher than 98.5%;

[0008] The structural formula of the highly efficient grafted natural polymer flocculant is:

[0009]

[0010] The preparation method of the highly efficient grafted natural polymer flocculant is as follows:

[0011] Step 1. Disperse the natural polymer in a sodium hydroxide or potassium hydroxide aqueous solution with a mass percentage concentration of 1-30% (the ratio of the natural polymer to the hydroxide aqueous solution is 1:2-1:5), and alkalize for 0.5-2h; then, add trimethyl-(3-chloro-2-hydroxy)propylammonium chloride, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to the natural polymer is 0.1:1-3:1, and react at 30-80°C for 0.5-4h. After the reaction is completed, use ethanol as a precipitant, precipitate and separate to obtain a cationic natural polymer;

[0012] Step 2. Dissolve the cationic natural polymer obtained in step 1 in water to prepare a solution with a mass percentage concentration of 1%-3% of the cationic natural polymer, add a reaction initiator, and then add a mixture of acrylamide and sodium allyl sulfonate, the amount of acrylamide added is: the mass ratio of acrylamide to the cationic natural polymer is 1:1-10:1, the amount of sodium allyl sulfonate added is: the mass ratio of sodium allyl sulfonate to the cationic natural polymer is 1:1-10:1, react at 45-65°C for 1-6 hours, then use ethanol or acetone as a precipitant to precipitate and separate the product to prepare a grafted amphoteric natural polymer flocculant.

[0013] Preferably, the preparation route of the highly efficient grafted natural polymer flocculant is as follows:

[0014]

[0015] Preferably, the degree of substitution of cationic groups in the efficient grafted natural polymer flocculant is 5%-99%, the mass of polyacrylamide is 5%-80% of the mass of the efficient grafted natural polymer flocculant, and the mass of sodium polyallyl sulfonate is 5%-70% of the mass of the efficient grafted natural polymer flocculant.

[0016] Preferably, the preparation method of the high-efficiency grafted natural polymer flocculant is as follows: starch (Shandong Binzhou Jinhui Corn Development Co., Ltd., weight average molecular weight of about 150,000) is dispersed in a 5% sodium hydroxide aqueous solution (the ratio of starch to sodium hydroxide aqueous solution is 1:4), and alkalized at 70°C for 1h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to starch is 2:1, and the reaction is carried out at 70°C for 2h; after the reaction is completed, ethanol is used as a precipitant , precipitate and separate to obtain cationic starch, dissolve the cationic starch in water, prepare a solution with a mass percentage concentration of 1% of cationic starch, add ammonium persulfate as an initiator (the amount added is 2% of the molar number of starch units) after the solution is uniform, and then add acrylamide (with a mass ratio of 5:1 to cationic starch) and sodium allyl sulfonate (with a mass ratio of 3:1 to cationic starch) mixture, react at 45°C for 4 hours, and then use acetone as a precipitant to precipitate and separate the product, that is, obtain a grafted amphoteric starch flocculant. According to the analysis by nuclear magnetic method, the degree of substitution of the cationic group is 90%, the content of polyacrylamide is 40% (mass), and the content of sodium polyallyl sulfonate is 31% (mass). The solubility experiment shows that its maximum solubility is: at 25°C, 21g of grafted amphoteric starch flocculant product is dissolved in 100g of water.

[0017] Preferably, cellulose is dispersed in a 1% potassium hydroxide aqueous solution (the ratio of cellulose to sodium hydroxide aqueous solution is 1:5), and alkalized at 20°C for 2h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to cellulose is 3:1, and the reaction is carried out at 30°C for 0.5h; after the reaction is completed, ethanol is used as a precipitant to precipitate and separate to obtain cationic cellulose, and the cationic cellulose is dissolved in water to prepare a solution with a mass percentage concentration of 2% of the cationic cellulose. After the solution is uniform, ammonium persulfate is added as an initiator (the amount added is 3% of the molar number of cellulose units), and then acrylamide (with a mass ratio of cationic cellulose of 1:1) and sodium allyl sulfonate (with a mass ratio of cationic cellulose of 8:1) are added, and the reaction is carried out at 50°C for 6 hours, and then ethanol is used as a precipitant to precipitate and separate the product, that is, a grafted amphoteric cellulose flocculant is obtained. According to the analysis by nuclear magnetic method, the degree of substitution of cationic groups is 98%, the content of polyacrylamide is 5% (mass), and the content of sodium polyallyl sulfonate is 65% (mass). The solubility experiment shows that the maximum solubility is: 27g of the grafted amphoteric cellulose flocculant product is dissolved in 100g of water at 25°C.

[0018] Preferably, the flocculant is used as simulated water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge) with different charges, and its actual flocculation effect is observed by a spectrophotometer (wavelength 630nm) and an ultraviolet spectrophotometer (wavelength 254nm). For the kaolin suspension, when the amount of the flocculant is 0.1-0.5mg / L in the pH range of 2-9, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%; for the humic acid aqueous solution, when the amount of the flocculant is 2.0-7.5mg / L in the pH range of 3-9, the flocculation effect is good, and the humic acid removal rate of the treated water sample is higher than 98.5%; for the hematite suspension, when the amount of the flocculant is 0.2-1mg / L in the pH range of 4-11, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

[0019] Preferably, the preparation method of the high-efficiency grafted natural polymer flocculant is as follows: chitosan is dispersed in a 20% potassium hydroxide aqueous solution (the ratio of chitosan to potassium hydroxide aqueous solution is 1:3), and alkalized at 40°C for 1h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to chitosan is 0.5:1, and the reaction is carried out at 50°C for 3h; after the reaction is completed, ethanol is used as a precipitant, and the cationic chitosan is separated by precipitation to obtain Chitosan is prepared by dissolving cationic chitosan in water to prepare a solution with a mass percentage concentration of 2% of cationic chitosan. After the solution is uniform, ammonium cerium nitrate is added as an initiator (the amount added is 2% of the molar number of chitosan units), and then acrylamide (with a mass ratio of 2:1 to cationic chitosan) and sodium allyl sulfonate (with a mass ratio of 10:1 to cationic chitosan) are added, and the reaction is carried out at 60°C for 5 hours. Then, acetone is used as a precipitant to precipitate and separate the product, and a grafted amphoteric chitosan flocculant is obtained. According to the analysis by nuclear magnetic method, the degree of substitution of the cationic group is 39%, the content of polyacrylamide is 10% (mass), and the content of sodium polyallyl sulfonate is 68% (mass). The solubility experiment shows that the maximum solubility is: at 25°C, 24g of the grafted amphoteric chitosan flocculant product is dissolved in 100g of water.

[0020] Preferably, the flocculant is used with kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge) as simulated water samples, and its actual flocculation effect is observed by a spectrophotometer (wavelength 630nm) and an ultraviolet spectrophotometer (wavelength 254nm). For the kaolin suspension, when the amount of the flocculant is 0.8-2mg / L in the pH range of 2-8, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98%; for the humic acid aqueous solution, when the amount of the flocculant is 3.0-9.5mg / L in the pH range of 3.5-10, the flocculation effect is good, and the humic acid removal rate of the treated water sample is higher than 98.5%; for the hematite suspension, when the amount of the flocculant is 0.1-0.5mg / L in the pH range of 4-11, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

[0021] A highly efficient grafted amphoteric natural polymer flocculant, which is obtained by grafting copolymerization of cationic polymer with acrylamide and sodium allyl sulfonate.

[0022] The above-mentioned grafted amphoteric natural polymer flocculant, the natural polymer includes: starch, cellulose, chitin; the cationic natural polymer is a cationic natural polymer obtained by reacting natural polymer and trimethyl-(3-chloro-2-hydroxy)propylammonium chloride, wherein the natural polymer can adopt commercially available natural polymer materials.

[0023] In the above method for preparing grafted amphoteric natural polymer flocculant, the initiator is ammonium cerium nitrate or ammonium persulfate, and the molar number of the initiator is 1%-3% of the molar number of the natural polymer unit.

[0024] Beneficial effects:

[0025] The grafted amphoteric natural polymer flocculant material prepared by the preparation method of the present invention has the triple characteristics of cationic group, polyacrylamide and sodium polyallyl sulfonate; and the three are linked by chemical bonds, which increases the molecular weight of the natural polymer, improves the water solubility of the natural polymer, and enhances its bonding, bridging and flocculation effect; in addition, since the cationic group carries a positive charge, and the carboxyl group on the sodium polyallyl sulfonate chain carries an anionic negative charge, it can be suitable for treating water bodies with different charges and has good salt resistance; and its application range is also wider, and it can be used in both acidic and alkaline media, and the pH range of adaptation is wide. Moreover, since the natural polymer is a natural biodegradable material, it has the characteristics of non-toxicity and no secondary pollution.

[0026] The preparation method of the grafted amphoteric natural polymer flocculant material of the present invention is simple to operate and can be prepared once by a continuous feeding method. The main raw materials used are natural polymer products with abundant sources, which is suitable for large-scale industrial production and is an economical preparation method for obtaining high-quality water treatment agents.

[0027] (1) Highly efficient grafted amphoteric natural polymer flocculant materials, which have amphoteric characteristics due to the rich anionic and cationic groups on the molecular chain, not only improve the flocculation performance of the material, but also improve the solubility of the natural polymer;

[0028] (2) Polymer materials are widely available and inexpensive, and grafted amphoteric natural polymer flocculant materials have a high cost-effectiveness ratio;

[0029] (3) Natural polymers are biodegradable and non-toxic, and will not cause secondary pollution to water bodies;

[0030] (4) Compared with polyacrylamide flocculants, the mass ratio of acrylamide added to the final flocculant in the product of the present invention is greatly reduced, which greatly reduces the pollution risk of acrylamide monomers;

[0031] (5) The product has many functions including good flocculation, metal ion adsorption, antibacterial, deodorization, decolorization and effective reduction of COD value;

[0032] (6) The product is highly efficient with a low dosage, generally 0.1-0.5 mg / L. It can be used to treat water bodies with different charges, has good salt resistance, and has a wide pH range of 1-12. It can be used to treat kaolin suspension, humic acid aqueous solution, and hematite suspension. The pollutant removal rate of the treated water samples is higher than 98.5%.

[0033] (7) The product is suitable for treating water bodies with different charges, has good salt resistance, and has a wide pH range of 2-11. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Infrared spectra of (1) starch, (2) cationic starch and (3) grafted amphoteric starch flocculant materials.

[0035] Figure 2 Schematic diagram of the flocculation effect of grafted amphoteric starch flocculant material on negatively charged kaolin suspension.

[0036] Figure 3 Schematic diagram of the flocculation effect of grafted amphoteric starch flocculant material on negatively charged humic acid aqueous solution.

[0037] Figure 4 Schematic diagram of the flocculation effect of grafted amphoteric starch flocculant material on a positively charged hematite powder suspension.

[0038] Figure 5 Schematic diagram of the effect of water pH on the flocculation performance of grafted amphoteric starch flocculant materials. DETAILED DESCRIPTION

[0039] The present invention is further described below by way of examples. It should be understood that these examples are explanations and examples of the present invention and are not intended to limit the scope of the present invention in any form.

[0040] Embodiment 1:

[0041] Starch (Shandong Binzhou Jinhui Corn Development Co., Ltd., weight average molecular weight of about 150,000) was dispersed in 5% sodium hydroxide aqueous solution (ratio of starch to sodium hydroxide aqueous solution was 1:4), alkalized at 70°C for 1h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to starch was 2:1, and reacted at 70°C for 2h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic starch, the cationic starch was dissolved in water, and a solution with a mass percentage concentration of 1% of cationic starch was prepared. After the solution was uniform, ammonium persulfate was added as an initiator (the amount added was 2% of the molar number of starch units), and then a mixture of acrylamide (mass ratio to cationic starch was 5:1) and sodium allyl sulfonate (mass ratio to cationic starch was 3:1) was added, and reacted at 45°C for 4 hours, and then acetone was used as a precipitant to precipitate and separate the product, that is, a grafted amphoteric starch flocculant was obtained.

[0042] The preparation route of the highly efficient grafted natural polymer flocculant is as follows:

[0043]

[0044] The results of nuclear magnetic resonance analysis showed that the degree of substitution of the cationic groups was 90%, the content of polyacrylamide was 40% (mass), and the content of sodium polyallyl sulfonate was 31% (mass).

[0045] Infrared spectra of starch, cationic starch and grafted amphoteric starch flocculant materials are shown in Figure 1 ,from Figure 1 The wave number is about 3270cm -1 It is the characteristic absorption peak of O-H; 1477cm -1 It is the characteristic absorption peak of quaternary ammonium salt cationic group, which proves that the cationic starch was successfully prepared, and 1660cm -1 The amide stretching vibration peaks around 1554 cm -1 The sulfonate stretching vibration peaks at around 2.0 further indicate that polyacrylamide and sodium polyallyl sulfonate have been grafted onto the starch molecular skeleton.

[0046] The solubility experiment shows that the maximum solubility is: 21g of grafted amphoteric starch flocculant product is dissolved in 100g of water at 25°C.

[0047] The flocculant was used with kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge) with different charges as simulated water samples. When the pH was 7, the kaolin suspension and the hematite suspension were measured by a spectrophotometer (wavelength 630nm) to observe their actual flocculation effects; the humic acid aqueous solution was measured by an ultraviolet spectrophotometer (wavelength 254nm) to observe its actual flocculation effect. Figure 2, Figure 3 and Figure 4 The actual flocculation effect diagram of the flocculant using kaolin suspension, humic acid aqueous solution and hematite suspension as simulated water samples. As can be seen from the figure, for kaolin suspension, when the flocculant dosage is 0.3mg / L, the flocculation effect is the best, and the turbidity removal rate of the water sample is more than 98.5%; for humic acid aqueous solution, when the flocculant dosage is 2.5mg / L, the flocculation effect is the best, and the humic acid removal rate of the water sample is higher than 98.5%; for hematite suspension, when the flocculant dosage is 0.4mg / L, the flocculation effect is the best, and the turbidity removal rate of the water sample is more than 98.5%. The removal rates of kaolin and hematite in the samples without flocculant are only about 20%, and the removal rate of humic acid is 0.

[0048] In addition, kaolin suspension, humic acid aqueous solution and hematite suspension were used as simulated water samples, and their actual flocculation effects were observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm) in the range of pH = 1-13. Figure 5 As shown, for kaolin suspension, in the range of pH = 2-10, the turbidity removal rate of the water sample after treatment is higher than 98.5%; for humic acid aqueous solution, in the range of pH = 2-10, the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 3-11, the turbidity removal rate of the water sample after treatment is higher than 98.5%.

[0049] Embodiment 2:

[0050] The cellulose was dispersed in a 1% potassium hydroxide aqueous solution (the ratio of cellulose to sodium hydroxide aqueous solution was 1:5), and alkalized at 20°C for 2h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to cellulose was 3:1, and the reaction was carried out at 30°C for 0.5h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic cellulose, and the cationic cellulose was dissolved in water to prepare a solution with a mass percentage concentration of 2% of the cationic cellulose. After the solution was uniform, ammonium persulfate was added as an initiator (the amount added was 3% of the molar number of cellulose units), and then acrylamide (with a mass ratio of 1:1 to the cationic cellulose) and sodium allyl sulfonate (with a mass ratio of 8:1 to the cationic cellulose) were added, and the reaction was carried out at 50°C for 6 hours, and then ethanol was used as a precipitant to precipitate and separate the product, that is, a grafted amphoteric cellulose flocculant was obtained. The results of nuclear magnetic resonance analysis showed that the degree of substitution of the cationic groups was 98%, the content of polyacrylamide was 5% (mass), and the content of sodium polyallyl sulfonate was 65% (mass).

[0051] The solubility experiment shows that the maximum solubility is: 27g of the grafted amphoteric cellulose flocculant product is dissolved in 100g of water at 25°C.

[0052] The flocculant was used as simulated water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge) with different charges, and its actual flocculation effect was observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH=2-9, when the amount of flocculant was 0.1-0.5mg / L, the flocculation effect was good, and the turbidity removal rate of the water sample was more than 98.5%; for humic acid aqueous solution, in the range of pH=3-9, when the amount of flocculant was 2.0-7.5mg / L, the flocculation effect was good, and the humic acid removal rate of the treated water sample was higher than 98.5%; for hematite suspension, in the range of pH=4-11, when the amount of flocculant was 0.2-1mg / L, the flocculation effect was good, and the turbidity removal rate of the water sample was more than 98.5%.

[0053] Embodiment 3:

[0054] The starch was dispersed in a 15% sodium hydroxide aqueous solution (the ratio of starch to sodium hydroxide aqueous solution was 1:3.5), and alkalized at 40°C for 2h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to starch was 1.5:1, and the reaction was carried out at 45°C for 4h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic starch, and the cationic starch was dissolved in water to prepare a solution with a mass percentage concentration of 3% of cationic starch. After the solution was uniform, ammonium cerium nitrate was added as an initiator (the amount added was 1% of the molar number of starch units), and then acrylamide (with a mass ratio of cationic starch of 3:1) and sodium allyl sulfonate (with a mass ratio of cationic starch of 6:1) were added, and the reaction was carried out at 60°C for 3 hours, and then acetone was used as a precipitant to precipitate and separate the product, that is, a grafted amphoteric starch flocculant was obtained. According to the analysis by nuclear magnetic method, the degree of substitution of cationic groups is 55%, the content of polyacrylamide is 26% (mass), and the content of sodium polyallyl sulfonate is 51% (mass). The solubility experiment shows that the maximum solubility is: 20g of grafted amphoteric starch flocculant product is dissolved in 100g of water at 25°C. The flocculant is used as simulated water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect is observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH = 2-8, when the dosage of flocculant is 0.4-1.5 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%; for humic acid aqueous solution, in the range of pH = 2-9, when the dosage of flocculant is 3.0-8.5 mg / L, the flocculation effect is good, and the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 4-11, when the dosage of flocculant is 0.3-1.2 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%.

[0055] Embodiment 4:

[0056] The chitosan was dispersed in a 20% potassium hydroxide aqueous solution (the ratio of chitosan to potassium hydroxide aqueous solution was 1:3), and alkalized at 40°C for 1 hour; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to chitosan was 0.5:1, and the reaction was carried out at 50°C for 3 hours; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic chitosan, and the cationic chitosan was dissolved in water to prepare a solution with a mass percentage concentration of 2% of cationic chitosan. After the solution was uniform, ammonium cerium nitrate was added as an initiator (the amount added was 2% of the molar number of chitosan units), and then acrylamide (with a mass ratio of 2:1 to cationic chitosan) and sodium allyl sulfonate (with a mass ratio of 10:1 to cationic chitosan) were added, and the reaction was carried out at 60°C for 5 hours, and then acetone was used as a precipitant to precipitate and separate the product, so as to obtain a grafted amphoteric chitosan flocculant. The nuclear magnetic method was used to analyze that the degree of substitution of the cationic group was 39%, the content of polyacrylamide was 10% (mass), and the content of sodium polyallyl sulfonate was 68% (mass). The solubility experiment showed that the maximum solubility was: 24g of the grafted amphoteric chitin flocculant product was dissolved in 100g of water at 25°C. The flocculant was used to simulate the water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect was observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH = 2-8, when the dosage of flocculant is 0.8-2 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98%; for humic acid aqueous solution, in the range of pH = 3.5-10, when the dosage of flocculant is 3.0-9.5 mg / L, the flocculation effect is good, and the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 4-11, when the dosage of flocculant is 0.1-0.5 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

[0057] Embodiment 5:

[0058] The cellulose was dispersed in a 30% potassium hydroxide aqueous solution (the ratio of cellulose to the potassium hydroxide aqueous solution was 1:2), and alkalized at 50°C for 0.5h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to cellulose was 0.1:1, and the reaction was carried out at 80°C for 4h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic cellulose, and the cationic cellulose was dissolved in water to prepare a solution with a mass percentage concentration of 3% of the cationic cellulose. After the solution was uniform, ammonium cerium nitrate was added as an initiator (the amount added was 3% of the molar number of cellulose units), and then acrylamide (with a mass ratio of 10:1 to the cationic cellulose) and sodium allyl sulfonate (with a mass ratio of 1:1 to the cationic cellulose) were added, and the reaction was carried out at 65°C for 2 hours, and then ethanol was used as a precipitant to precipitate and separate the product, so as to obtain a grafted amphoteric cellulose flocculant. The nuclear magnetic method was used to analyze that the degree of substitution of the cationic group was 5%, the content of polyacrylamide was 79% (mass), and the content of sodium polyallyl sulfonate was 5% (mass). The solubility experiment showed that the maximum solubility was: 14g of the grafted amphoteric cellulose flocculant product was dissolved in 100g of water at 25°C. The flocculant was used to simulate the water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect was observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH = 2-8, when the dosage of flocculant is 2-6 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%; for humic acid aqueous solution, in the range of pH = 3-10, when the dosage of flocculant is 3.0-7.5 mg / L, the flocculation effect is good, and the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 5-11, when the dosage of flocculant is 1.2-8 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%.

[0059] Embodiment 6:

[0060] The starch was dispersed in a 25% sodium hydroxide aqueous solution (the ratio of starch to sodium hydroxide aqueous solution was 1:2.5), and alkalized at 30°C for 1.5h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to starch was 2.5:1, and the reaction was carried out at 40°C for 1h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic starch, and the cationic starch was dissolved in water to prepare a solution with a mass percentage concentration of 1% of cationic starch. After the solution was uniform, ammonium persulfate was added as an initiator (the amount added was 1% of the molar number of starch units), and then acrylamide (with a mass ratio of cationic starch of 6:1) and sodium allyl sulfonate (with a mass ratio of cationic starch of 2:1) were added, and the reaction was carried out at 65°C for 5 hours, and then acetone was used as a precipitant to precipitate and separate the product, that is, a grafted amphoteric starch flocculant was obtained. According to the analysis by nuclear magnetic method, the degree of substitution of cationic groups is 95%, the content of polyacrylamide is 44% (mass), and the content of sodium polyallyl sulfonate is 19% (mass). The solubility experiment shows that the maximum solubility is: 23g of grafted amphoteric starch flocculant product is dissolved in 100g of water at 25°C. The flocculant is used as simulated water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect is observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH = 2-9, when the dosage of flocculant is 0.2-1 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98%; for humic acid aqueous solution, in the range of pH = 3-9, when the dosage of flocculant is 2.5-8.5 mg / L, the flocculation effect is good, and the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 5-11, when the dosage of flocculant is 0.6-3 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

[0061] Embodiment 7:

[0062] The chitosan was dispersed in a 10% potassium hydroxide aqueous solution (the ratio of chitosan to sodium hydroxide aqueous solution was 1:4), and alkalized at 60°C for 1.5h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride was added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to chitosan was 1:1, and the reaction was carried out at 60°C for 1h; after the reaction was completed, ethanol was used as a precipitant to precipitate and separate to obtain cationic chitosan, and the cationic chitosan was dissolved in water to prepare a solution with a mass percentage concentration of 1% of cationic chitosan. After the solution was uniform, ammonium persulfate was added as an initiator (the amount added was 1% of the molar number of chitosan units), and then acrylamide (with a mass ratio of 8:1 to cationic chitosan) and sodium allyl sulfonate (with a mass ratio of 5:1 to cationic chitosan) were added, and the reaction was carried out at 55°C for 1h, and then ethanol was used as a precipitant to precipitate and separate the product to obtain a grafted amphoteric chitosan flocculant. The nuclear magnetic method was used to analyze that the degree of substitution of the cationic group was 68%, the content of polyacrylamide was 51% (mass), and the content of sodium polyallyl sulfonate was 32% (mass). The solubility experiment showed that the maximum solubility was: 20g of the grafted amphoteric chitosan flocculant product was dissolved in 100g of water at 25°C. The flocculant was used to simulate the water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect was observed by spectrophotometer (wavelength 630nm) and ultraviolet spectrophotometer (wavelength 254nm). For kaolin suspension, in the range of pH = 2-8, when the dosage of flocculant is 0.3-1.8 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%; for humic acid aqueous solution, in the range of pH = 4-10, when the dosage of flocculant is 2.0-8.5 mg / L, the flocculation effect is good, and the humic acid removal rate of the water sample after treatment is higher than 98.5%; for hematite suspension, in the range of pH = 4-11, when the dosage of flocculant is 0.4-1.2 mg / L, the flocculation effect is good, and the turbidity removal rate of the water sample is above 98.5%.

[0063] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for using a highly efficient grafted natural polymer flocculant for sewage treatment, characterized in that: The invention uses a high-efficiency grafted natural polymer flocculant for sewage treatment. The flocculant uses kaolin suspension, humic acid aqueous solution and hematite suspension as sewage samples to be treated. For kaolin suspension, when the flocculant dosage is 0.3 mg / L, the flocculation effect is the best, and the turbidity removal rate of the water sample is more than 98.5%; for humic acid aqueous solution, when the flocculant dosage is 2.5 mg / L, the flocculation effect is the best, and the humic acid removal rate of the water sample is more than 98.5%; for hematite suspension, when the flocculant dosage is 1.5 mg / L, the flocculation effect is the best, and the humic acid removal rate of the water sample is more than 98.5%; For the suspension, when the flocculant dosage is 0.4mg / L, the flocculation effect is the best, and the turbidity removal rate of the water sample is above 98.5%; for the kaolin suspension, in the pH range of 2-10, the turbidity removal rate of the water sample after treatment is higher than 98.5%; for the humic acid aqueous solution, in the pH range of 2-10, the humic acid removal rate of the water sample after treatment is higher than 98.5%; for the hematite suspension, in the pH range of 3-11, the turbidity removal rate of the water sample after treatment is higher than 98.5%; The structural formula of the highly efficient grafted natural polymer flocculant is: Wherein, m=50-1000, n=50-1000; The preparation method of the highly efficient grafted natural polymer flocculant is as follows: Step 1. Disperse the natural polymer in a sodium hydroxide or potassium hydroxide aqueous solution with a mass percentage concentration of 1-30% (the ratio of the natural polymer to the hydroxide aqueous solution is 1:2-1:5), and alkalize for 0.5-2h; then, add trimethyl-(3-chloro-2-hydroxy)propylammonium chloride, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to the natural polymer is 0.1:1-3:1, and react at 30-80°C for 0.5-4h. After the reaction is completed, use ethanol as a precipitant, precipitate and separate to obtain a cationic natural polymer; Step 2. Dissolve the cationic natural polymer obtained in step 1 in water to prepare a solution with a mass percentage concentration of 1%-3% of the cationic natural polymer, add a reaction initiator, and then add a mixture of acrylamide and sodium allyl sulfonate, the amount of acrylamide added is: the mass ratio of acrylamide to the cationic natural polymer is 1:1-10:1, the amount of sodium allyl sulfonate added is: the mass ratio of sodium allyl sulfonate to the cationic natural polymer is 1:1-10:1, react at 45-65°C for 1-6 hours, then use ethanol or acetone as a precipitant to precipitate and separate the product to prepare a grafted amphoteric natural polymer flocculant.

2. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The preparation route of the highly efficient grafted natural polymer flocculant is as follows:

3. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The cationic group substitution degree of the efficient grafted natural polymer flocculant is 5%-99%, the mass of polyacrylamide is 5%-80% of the mass of the efficient grafted natural polymer flocculant, and the mass of sodium polyallyl sulfonate is 5%-70% of the mass of the efficient grafted natural polymer flocculant.

4. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The preparation method of the high-efficiency grafted natural polymer flocculant is as follows: starch (Shandong Binzhou Jinhui Corn Development Co., Ltd., weight average molecular weight of about 150,000) is dispersed in a 5% sodium hydroxide aqueous solution (the ratio of starch to sodium hydroxide aqueous solution is 1:4), and alkalized at 70°C for 1h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to starch is 2:1, and the reaction is carried out at 70°C for 2h; after the reaction is completed, ethanol is used as a precipitant to precipitate and separate to obtain cationic starch, the cationic starch is dissolved in water, a solution with a mass percentage concentration of 1% of the cationic starch is prepared, and after the solution is uniform , add ammonium persulfate as an initiator (the amount added is 2% of the molar number of starch units), then add a mixture of acrylamide (with a mass ratio of 5:1 to cationic starch) and sodium allyl sulfonate (with a mass ratio of 3:1 to cationic starch), react at 45°C for 4 hours, then use acetone as a precipitant to precipitate and separate the product, thus obtaining a grafted amphoteric starch flocculant. According to nuclear magnetic resonance analysis, the degree of substitution of the cationic group is 90%, the content of polyacrylamide is 40% (mass), and the content of sodium polyallyl sulfonate is 31% (mass); the solubility experiment shows that the maximum solubility is: at 25°C, 21g of the grafted amphoteric starch flocculant product is dissolved in 100g of water.

5. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The preparation method of the high-efficiency grafted natural polymer flocculant is as follows: cellulose is dispersed in a 1% potassium hydroxide aqueous solution (the ratio of cellulose to sodium hydroxide aqueous solution is 1:5), and alkalized at 20°C for 2h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to cellulose is 3:1, and the reaction is carried out at 30°C for 0.5h; after the reaction is completed, ethanol is used as a precipitant to precipitate and separate to obtain cationic cellulose, the cationic cellulose is dissolved in water to prepare a solution with a mass percentage concentration of 2% of the cationic cellulose, and after the solution is uniform, ammonium persulfate is added as An initiator (the amount added is 3% of the molar number of cellulose units), acrylamide (the mass ratio to cationic cellulose is 1:1) and sodium allyl sulfonate (the mass ratio to cationic cellulose is 8:1), and the reaction is carried out at 50°C for 6 hours. Then, ethanol is used as a precipitant to precipitate and separate the product, thereby obtaining a grafted amphoteric cellulose flocculant. According to nuclear magnetic resonance analysis, the degree of substitution of the cationic group is 98%, the content of polyacrylamide is 5% (mass), and the content of sodium polyallyl sulfonate is 65% (mass). The solubility experiment shows that the maximum solubility is: at 25°C, 27g of the grafted amphoteric cellulose flocculant product is dissolved in 100g of water.

6. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The flocculant is used as simulated water samples, including kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge) with different charges, and its actual flocculation effect is observed by a spectrophotometer (wavelength 630nm) and an ultraviolet spectrophotometer (wavelength 254nm). For the kaolin suspension, when the amount of the flocculant is 0.1-0.5mg / L in the pH range of 2-9, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%; for the humic acid aqueous solution, when the amount of the flocculant is 2.0-7.5mg / L in the pH range of 3-9, the flocculation effect is good, and the humic acid removal rate of the treated water sample is higher than 98.5%; for the hematite suspension, when the amount of the flocculant is 0.2-1mg / L in the pH range of 4-11, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

7. The method for using the high-efficiency grafted natural polymer flocculant for sewage treatment according to claim 1, characterized in that: The preparation method of the high-efficiency grafted natural polymer flocculant is as follows: chitosan is dispersed in a 20% potassium hydroxide aqueous solution (the ratio of chitosan to potassium hydroxide aqueous solution is 1:3), and alkalized at 40°C for 1h; then, trimethyl-(3-chloro-2-hydroxy)propylammonium chloride is added, and the mass ratio of trimethyl-(3-chloro-2-hydroxy)propylammonium chloride to chitosan is 0.5:1, and the reaction is carried out at 50°C for 3h; after the reaction is completed, ethanol is used as a precipitant to precipitate and separate to obtain cationic chitosan, and the cationic chitosan is dissolved in water to prepare a solution with a mass percentage concentration of 2% of cationic chitosan, and after the solution is uniform, cerium ammonium nitrate is added as an initiator. The invention discloses a grafted amphoteric chitosan flocculant. The invention discloses a grafted amphoteric chitosan flocculant. The grafted amphoteric chitosan flocculant is prepared by mixing a precipitating agent (the amount of the chitosan flocculant is 2% of the molar number of the chitosan unit), and then adding acrylamide (the mass ratio of the chitosan to the cationic chitosan is 2:1) and sodium allyl sulfonate (the mass ratio of the chitosan to the cationic chitosan is 10:1), reacting at 60°C for 5 hours, and then using acetone as a precipitant to precipitate and separate the product, thereby obtaining a grafted amphoteric chitosan flocculant. The results of nuclear magnetic resonance analysis show that the degree of substitution of the cationic group is 39%, the content of polyacrylamide is 10% (mass), and the content of sodium polyallyl sulfonate is 68% (mass). The solubility experiment shows that the maximum solubility is: at 25°C, 24g of the grafted amphoteric chitosan flocculant product is dissolved in 100g of water.

8. The method for treating sewage using the high-efficiency grafted natural polymer flocculant according to claim 6, characterized in that: The flocculant is used as simulated water samples of kaolin suspension (negative charge), humic acid aqueous solution (negative charge) and hematite suspension (positive charge), and its actual flocculation effect is observed by a spectrophotometer (wavelength 630nm) and an ultraviolet spectrophotometer (wavelength 254nm). For the kaolin suspension, when the amount of the flocculant is 0.8-2mg / L in the pH range of 2-8, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98%; for the humic acid aqueous solution, when the amount of the flocculant is 3.0-9.5mg / L in the pH range of 3.5-10, the flocculation effect is good, and the humic acid removal rate of the treated water sample is higher than 98.5%; for the hematite suspension, when the amount of the flocculant is 0.1-0.5mg / L in the pH range of 4-11, the flocculation effect is good, and the turbidity removal rate of the water sample is more than 98.5%.

Citation Information

Patent Citations

  • Starch-based graft copolymer coal water slurry dispersant and preparation method thereof

    CN102351995A

  • Method for preparing amphoteric starch

    CN102585097A

  • Preparation method of grafted amphoteric starch flocculants

    CN103087265A

  • Graft dendrite copolymers, and methods for producing the same

    CN103889395A

  • Preparation method of starch grafting concrete thickener

    CN106632859A

Cited By

  • Amphoteric modified starch flocculant as well as preparation method and application thereof

    CN121064406A

  • Amphoteric modified starch flocculant, its preparation method and application

    CN121064406B